Catalytic degradation of aromatic dyes using triazolidine-thione stabilized nickel nanoparticles - Shahnaz; Attiya-E Rasool; Warda Parveen (Heliyon)
Nanoparticles have been extensively studied for many years due to their important roles in catalysis, metallurgy and high temperature superconductors. But, Nanoparticles are extremely unstable and easily react with other substances. So, to control the size and the shape of nanoparticles they must be stabilized. Organic Ligands have gain more attention for stabilizing Nanoparticles. In the present work, Nickel Nanoparticles have been synthesized by reduction method and then stabilized by synthesized 5-phenyl triazolidine-thione based organic ligand to achieve larger surface area and good catalytic activity. Stabilized Nickel NPs of different ratios were synthesized for analyzing their catalytic performance against dyes that has become one of the most serious environmental problem causing drastic water pollution. The prepared thione stabilized Nickel nanoparticles were confirmed by UV–Visible and Infrared Spectroscopy. UV/Vis analysis displayed the peak at 236 nm which confirms the metallic Ni NPs formation while, in FTIR peak around 720-750 cm−1 is due to the nickel and sulphur bond stretching vibrations. The size, surface morphology and the quality of the stabilized Ni Nanoparticles were analyzed by Scanning Electron Microscopy (SEM) and X-Ray Diffraction (XRD) analysis. SEM images showed uneven morphology with variously sized and shaped particles. Large surface area is visible which is advantageous for catalytic degradation of pollutants. The degradation process was studied by using UV–visible Spectroscopy. The catalytic behavior of stabilized nanoparticles was evaluated by using various parameters i.e. time, concentration and size of NPs. These parameters were optimized during degradation process to get maximum degradation in short period of time. Maximum percentage degradation of Methylene blue, Methyl Orange and Rhodamine B dyes were achieved up to 90 %, 88 % and 81 % respectively, in short duration of time. All the three ratios of thione stabilized Ni Nanoparticles showed good degrading performance for all dyes, but 1:2 thione stabilized Ni NPs had shown maximum catalytic performance.